Pengaruh Promosi dan Fasilitas terhadap Keputusan Wisatawan Berkunjung pada Rumah Pohon Habitat Langkat - Ananda, Rahayu Sri; Winata, Edi (Journal of Management and Economics Research, 2023)
The purpose of this research was to found out whether there was an influenced of promotion and facilities on the decision of tourists visiting the Rumah Pohon Habitat Langkat. The sample of this research was 200 visitors at the Rumah Pohon Habitat, sampling used accidental sample. Data analysis used multiple linear regression tests, hypothesis test used the coefficient of determination test (R2), partial test (t test) and simultaneous test (F test), used SPSS 20 data processing. The results showed that promotion and facilities was positive and significant effects partially or simultaneously to the decisions of tourists visiting the Rumah Pohon Habitat.